2011
DOI: 10.4315/0362-028x.jfp-10-552
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Escherichia coli O157:H7, Salmonella Typhimurium, and Listeria monocytogenes in Orange and Tomato Juice Using Ohmic Heating

Abstract: The effects of ohmic heating on reduction of Escherichia coli O157:H7, Salmonella Typhimurium, and Listeria monocytogenes in orange and tomato juice were investigated. Orange and tomato juice inoculated with E. coli O157:H7, Salmonella Typhimurium, and L. monocytogenes were subjected to ohmic heating with selected parameters including electric field strength from 10 to 20 V/cm and treatment times from 0 to 540 s. The number of pathogens was reduced by increasing the electric field strength from 10 to 20 V/cm a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 30 publications
1
17
1
Order By: Relevance
“…In general, reduction of E. coli O157:H7, S. Typhimurium and L. monocytogenes increased as ohmic heating temperature and treatment time increased in orange juice. These results are similar to those of Lee et al (2012) and Sagong et al (2011). In our study, the effect of inactivation was progressively greater as temperature increased at lower pH.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In general, reduction of E. coli O157:H7, S. Typhimurium and L. monocytogenes increased as ohmic heating temperature and treatment time increased in orange juice. These results are similar to those of Lee et al (2012) and Sagong et al (2011). In our study, the effect of inactivation was progressively greater as temperature increased at lower pH.…”
Section: Discussionsupporting
confidence: 94%
“…Newly spotlighted ohmic heating as an alternative to conventional heat treatment is effective due to not only the thermal effect of internal heat generation, but also the non-thermal effect of electropermeabilization (usually electroporation), which leads to enormous inactivation of microorganisms, especially foodborne pathogens. Several studies have been performed on inactivation by ohmic heating (Baysal & Icier, 2010;Lee et al, 2012;Park & Kang, 2013;Sagong et al, 2011). Park and Kang (2013) demonstrated the effect of electroporation by ohmic heating for inactivation of foodborne pathogens by comparing conventional heating with ohmic heating.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although numerous research studies of ohmic heating inactivation of microorganisms have been reported (28)(29)(30)(31), to our knowledge there is no information concerning the inactivation of E. coli O157:H7, and S. Typhimurium in solid-liquid food mixtures using high-frequency ohmic heating. The treatment time required to reduce E. coli O157:H7 and S. Typhimurium to below the detection limit (1 log CFU/g) decreased as the frequency increased.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the latter, the comparative ability of several L. monocytogenes and Salmonella spp. strains to survive under various interventions has been extensively studied in both laboratory media and foodstuffs (Carpenter, Smith, & Broadbent, 2011;Gomez-Aldapa et al, 2011;Menz, Vriesekoop, Zarei, Zhu, & Aldred, 2010;Nightingale, Thippareddi, Phebus, Marsden, & Nutsch, 2006;Porto-Fett et al, 2008Sagong, Park, Choi, Ryu, & Kang, 2011;Tiganitas, Zeaki, Gounadaki, Drosinos, & Skandamis, 2009). In the present study L. monocytogenes strain under study seemed more capable in surviving than S. typhimurium strain, especially at low and medium initial inocula, whereas no significant differences in the survival at high initial inocula were observed.…”
Section: Discussionmentioning
confidence: 99%